The occurrence of musculoskeletal injuries in nursing professionals: an analysis of Portuguese hospitals - Machado, Emílio Manuel (2011)
The motivation to perform this particular research comes from a need which we feel exists for further research in this area. It is necessary to answer a set of questions both empirical (observed over the years in the area of health and safety) and theoretical (following an analysis of the international literature) relative to the dimension of the problem of musculoskeletal injuries resulting from the exercise of the nursing profession in a hospital context. Research questions addressed include: 1) Are there complaints associated to the performing of nursing tasks? 2) How serious in terms of absolute numbers are musculoskeletal injuries? 3) What sort of influence does the environment (namely buildings) play, as well as technology / equipment, and work organization? Furthermore, 4) What should be present in the workplace but is not? After analyzing survey (of 168 active nurses in Portuguese hospitals) and interview data and having observed nurses at work, accompanying them in their day-to-day tasks, there is a global tendency to consider that, over the last twelve months of work, in a hospital context, nursing professionals have felt pain or musculoskeletal discomfort in a part of their bodies. Research results point also to more training and more adequate working spaces being needed in order to decrease musculoskeletal injuries amongst nurses. Furthermore, the more widespread usage of technological means which are lacking in some hospitals (such as beds with adjustable height, trapeze-type supporting bars attached above beds, patient transferring lifts and transferring belts) or in bad condition (such as wheels on beds, wheelchairs, and stretchers, which makes moving patients difficult) could also reveal itself to be an important aid, presenting itself as a solution to the problem discussed herein, on the one hand due to the number of injuries on the other due to the need for more professionals.